Perancangan Tempat Jemuran Buah Pinang dengan Pendekatan Ergonomi untuk Mengurangi Beban Kerja - Sahria Sahria; Nilda Tri Putri (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
The working conditions are not attention to comfort, satisfaction, safety and occupational health will certainly affect human physical workload. In design or redesign the workstation is should be considered the role and functions of the principal components of the system involved are human labor, machine/equipment, and physical work environment. The processing of betel nut through several steps. The step that requires a long time is the drying process, where the drying process using a clothesline with working conditions that do not attention to the principles of ergonomics and can lead to complaints of physical workload or musculoskeletal system. Results of the analysis that has been done can be seen that the working conditions after doing this design would be better than working conditions before the draft because the size of the clothesline was adjusted with anthropometry workers. The size of the design is the result of a high clothesline maximum betel 143.21 cm, 114.46 cm minimum height, the length of clothesline 135.92 cm and 122.98 cm wide.Keywords: Anthropometry, Workload, Ergonomics, Design.